Preparation method of carboxyl-metal ion complexing anti-pollution nanofiltration membrane
By forming an amino and carboxy group layer on the surface of the nanofiltration membrane and complexing with divalent metal ions, the problem of insufficient binding force of the modified layer in the prior art is solved, and efficient anti-pollution and water flux increase is achieved. Suitable for complex water treatment.
Patent Information
- Application Number
- CN202310794675.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing nanofiltration membrane surface modification methods are complex in operation, high in cost, and insufficient binding force of the modified layer, resulting in limited membrane separation efficiency and service life in complex water bodies.
Using the preparation method of carboxyl-metal ion complexing anti-pollution nanofiltration membrane, the nanofiltration membrane is reacted in a solution of polyphenol compounds to form an amino group layer, and then a carboxyl group is formed in a solution of succinic anhydride, and finally in a divalent A stable carboxyl-metal ion complex layer is formed in the metal salt solution, and the modified layer is firmly adhered by covalent bonds and electrostatic attraction.
It significantly improves the water flux and anti-pollution performance of the nanofiltration membrane, and the modified layer is stable and difficult to fall off, adapts to water quality fluctuations, reduces production costs and protects the environment.
Smart Images

Figure CN119215660A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment science and technology, in particular to a method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane. Background Art
[0002] With the growth of population and the continuous advancement of urbanization, the problem of water shortage is becoming more and more serious worldwide. Membrane separation technology is a powerful weapon to deal with this global problem of water shortage; in particular, reverse osmosis, a membrane technology with fine separation function, has played an important role in many aspects such as seawater desalination and sewage reuse.
[0003] However, membrane fouling is the main problem that hinders the membrane from performing effectively in the application of membrane separation technology, especially in complex water bodies with high salt content, which will seriously affect the membrane separation efficiency and service life. Therefore, based on the modification of the surface of the reverse osmosis nanofiltration membrane to achieve a certain anti-pollution effect, the separation performance and service life of the membrane can be improved.
[0004] Modification of the surface of the nanofiltration membrane has the characteristics of simple operation and mild reaction conditions, and no complex equipment is required in the reaction. For example, the invention patent CN111974231A forms a hydrophilic film on the surface of the polyamide desalting layer by immersing the synthesized polyamide membrane in a solution containing catechol, which improves the hydrophilicity of the nanofiltration membrane surface and has certain anti-fouling properties; the invention patent CN103480284A mixes nanosilver particles with a polyvinyl alcohol solution and applies it to the surface of the nanofiltration membrane to obtain a pollution-resistant polyamide nanofiltration membrane; the invention patent CN108671772A pre-treats the surface of the nanofiltration membrane, and then deposits a phytic acid-metal ion complex functional surface layer on the modified membrane to obtain a composite nanofiltration membrane with excellent separation function and anti-fouling performance. However, the above membrane surface modification methods are complicated to operate and have high costs, which are not conducive to practical use.
[0005] Invention patent CN103263859A provides a biomimetic mineralization preparation method for a polyelectrolyte / calcium carbonate composite nanofiltration membrane, wherein the treated base membrane is immersed in a cationic polyelectrolyte solution, and then transferred to an anionic polyelectrolyte solution. The cationic polyelectrolyte and the anionic polyelectrolyte form a polyelectrolyte composite membrane through electrostatic action, and then the membrane is fully washed and dried for standby use. In this method, the anionic polyelectrolyte combines with the cationic polyelectrolyte by electrostatic force, hydrogen bond, and hydrophobic force, and the formed modified layer has weak binding force and is easy to fall off.
[0006] In view of this, technicians urgently need to develop a simple, easy-to-obtain, and better anti-pollution method for nanofiltration membrane surface modification. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane. The method adopted by the present invention is simple and easy to operate, has a mild reaction, and is low in cost. The surface of the nanofiltration membrane is modified so that the surface has divalent metal ions, thereby achieving an anti-pollution function, and has a wide range of application value in the field of water treatment.
[0008] The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane provided by the present invention comprises the following steps:
[0009] S1: Using a nanofiltration membrane as a base membrane, immersing one side of the base membrane in a polyphenol compound solution to react, so that a polyphenol compound layer is formed on its surface with abundant amino groups, and then washing with deionized water to obtain a surface functionalized base membrane;
[0010] S2: soaking the surface functionalized base membrane obtained in step S1 in an organic solution containing an organic compound, stirring to allow the membrane surface to carry carboxyl groups, washing with deionized water and drying to obtain a nanofiltration membrane with carboxyl groups on the surface;
[0011] S3: soaking the nanofiltration membrane with carboxyl groups on the surface obtained in step S2 in a water-soluble divalent metal salt solution, stirring the membrane to form a carboxyl-metal ion complex layer, washing and drying to obtain a carboxyl-metal ion complex nanofiltration membrane with anti-pollution properties.
[0012] Preferably, in step S1, the nanofiltration membrane is a polyamide nanofiltration membrane. The concentration of the polyphenol compound solution is 0.5-2 g / L; the polyphenol compound solution is a mixed solution of dopamine and polyethyleneimine, and the mass ratio of dopamine to polyethyleneimine is 1:(1-3). The reaction conditions are: rotation speed 80-150 rpm, reaction temperature 40°C, reaction time 0.5-1.5 h.
[0013] When modifying the surface of the polyamide nanofiltration membrane, dopamine and polyethyleneimine are first used for modification, so that a gray-brown polyphenol compound layer is formed on the membrane surface, and many amino groups are covalently bonded to the membrane surface; the generated polyphenol compound layer can not only provide more amino groups for subsequent modification operations, but also increase the water flux of the base membrane.
[0014] Compared with CN103263859A, the present invention adopts a chemical method to modify the membrane surface. The formed modified layer is very firmly bonded and not easy to fall off due to the effects of covalent bonding and electrostatic attraction. It also has a good anti-pollution effect when there are large fluctuations in water quality and water volume.
[0015] Preferably, in step S2, the concentration of the organic solution containing the organic compound is 0.5-5 g / L. The organic solution containing the organic compound is an anhydrous ethanol solution containing succinic anhydride. The stirring conditions are: mechanical stirring, a rotation speed of 150-300 rpm, a temperature of 20-30° C., and a stirring time of 12-36 hours.
[0016] At the beginning of the experiment, dimethylformamide (DMF) was used as the organic solvent for succinic anhydride. Succinic anhydride had a good dissolving effect in it, but dimethylformamide was corrosive to the polyphenol compound layer formed at the beginning, causing the polyphenol compound layer to fall off, resulting in the inability to complete the subsequent modification operation. In addition, dimethylformamide has an unpleasant smell, is highly toxic, and is expensive. After many attempts, the best technical solution was finally obtained: using anhydrous ethanol as the organic solvent for succinic anhydride. Succinic anhydride is soluble in anhydrous ethanol, and ethanol will not damage the generated polyphenol compound layer. At the same time, anhydrous ethanol has low toxicity and is cheap.
[0017] After forming a modified layer rich in amino groups on the surface of the nanofiltration membrane, the present invention uses succinic anhydride to react with amino groups to generate carboxyl groups on the membrane surface, and at the same time generates water molecules, so that the membrane surface carries negative charges and the hydrophilicity of the membrane can also be improved. The modification method of the present invention significantly improves the water flux of the membrane, which is more than 20% higher than that before modification.
[0018] Succinic anhydride is used in the pharmaceutical industry to manufacture analgesics, diuretics, analgesics, antipyretics and anti-inflammatory drugs, and is rarely used in the field of water treatment technology. The inventors have found through a large number of experiments that succinic anhydride has a high efficiency in nucleophilic reaction with amino groups, a fast reaction time, and one mole of succinic anhydride can generate two moles of carboxyl groups, which greatly increases the amount of carboxyl groups generated. At the same time, succinic anhydride is relatively cheap, easy to obtain, and does not pollute the environment after use.
[0019] Preferably, in step S3, the mass concentration of the water-soluble divalent metal salt solution is 1-3%. The water-soluble divalent metal salt solution is a calcium chloride solution. The stirring conditions are: mechanical stirring, a rotation speed of 50-150 rpm, a temperature of 40-60° C., and a stirring time of 12-36 hours. The membrane is immersed in the divalent metal salt solution, and electrostatic action occurs, so that the calcium ions can be more closely combined with the carboxyl groups on the modified layer, thereby achieving an anti-pollution effect.
[0020] After obtaining negatively charged carboxyl groups on the surface of the modified membrane, the calcium ions in the cheap and readily available calcium chloride are combined with the modified carboxyl-rich surface of the nanofiltration membrane through electrostatic attraction, successfully introducing calcium ions into the surface of the nanofiltration membrane, forming a carboxyl-calcium ion complex layer on the membrane surface. This layer is not easy to fall off and has stable properties. It not only effectively improves the water flux of the polyamide nanofiltration membrane, but also does not reduce the retention rate of inorganic salts.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention mainly loads negatively charged functional groups on the membrane surface, and then deposits divalent metal salt ions on the membrane surface through covalent bonds and electrostatic attraction, so that positively charged metal ions are loaded on the membrane surface. Loading calcium ions on the membrane can effectively improve the hydrophilicity of the membrane surface, thereby increasing the flux of the membrane; and it hinders the complexing and bridging effect of divalent cations in water, while avoiding chemical bonding of soluble organic matter in water, and realizing anti-pollution function through electrostatic repulsion effect, which has a wide range of application value in the field of water treatment.
[0023] 2. When modifying the surface of the polyamide nanofiltration membrane, the present invention first uses dopamine and polyethyleneimine for modification. The generated polyphenol compound layer can not only provide more amino groups for subsequent modification operations, but also improve the water flux of the base membrane. Then, succinic anhydride is used for modification, so that the anhydride and the amino group undergo nucleophilic substitution reaction to generate carboxyl groups on the membrane surface; then, the membrane is immersed in a divalent metal salt solution to generate electrostatic action. Through covalent bonding and electrostatic attraction, the membrane is firmly bonded and not easy to fall off, and has a good anti-pollution effect when the water quality and water volume fluctuate greatly. The modification method of the present invention significantly improves the water flux of the membrane, which is more than 20% higher than that before modification.
[0024] 3. The method adopted by the present invention is simple and easy to operate, and the reaction is mild. At the same time, the raw materials used in the present invention are relatively economical and environmentally friendly, which is conducive to reducing production costs and protecting the environment: for example, succinic anhydride is relatively cheap, easy to obtain, and does not pollute the environment after use; and the loaded divalent soluble salt is also a cheap and easily available material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are morphology images of the membrane surfaces obtained in Examples 1 to 3 and Comparative Example 1, wherein (a) is the membrane surface morphology image of Comparative Example 1 (M0); (b) is the membrane surface morphology image of Example 1 (M1); (c) is the membrane surface morphology image of Example 2 (M2); and (d) is the membrane surface morphology image of Example 3 (M3).
[0026] Figure 2 It is the XPS analysis result of Examples 1 to 3 and Comparative Example 1.
[0027] Figure 3 A high pressure membrane performance test device was used to measure the pure water flux of the membranes of Examples 1 to 3 and Comparative Example 1 under a pressure of 10 bar. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Examples 1 to 3 and Comparative Example 1:
[0030] A method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane, the specific steps are as follows:
[0031] (1) The polyamide nanofiltration membrane was immersed in deionized water for 24 hours and then immersed in anhydrous ethanol for 2 hours to remove impurities on the membrane surface, thereby obtaining comparative example 1, referred to as M0, as a control sample.
[0032] The pretreated polyamide nanofiltration membrane was placed in a polytetrafluoroethylene closed box (single-sided reaction box), 1 g / L dopamine and 1 g / L polyethyleneimine were added, and after adjusting the pH to 8.5 with Tris-HCl (50 mM), it was placed in a shaker and reacted at 100 rpm and 40°C for 1 hour until a yellow-brown PDA / PEI layer appeared on the membrane; it was then rinsed three times with deionized water and blown dry with N2 to obtain a dopamine / polyethyleneimine-coated polyamide nanofiltration membrane.
[0033] (2) preparing 80 mL of anhydrous ethanol solution of succinic anhydride at a concentration of 1 g / L, and then immersing the obtained dopamine / polyethyleneimine coated polyamide nanofiltration membrane in the anhydrous ethanol solution of succinic anhydride, and mechanically stirring at 200 rpm and 20° C. for 24 h; after washing with deionized water, drying in a forced air drying oven at 60° C. for 10 min, obtaining a polyamide nanofiltration membrane having carboxyl functional groups on the surface.
[0034] (3) Calcium chloride solutions with mass concentrations of 1%, 2% and 3% were prepared respectively, and the polyamide nanofiltration membrane containing carboxyl functional groups on the surface was immersed in the calcium chloride solutions with mass concentrations of 1%, 2% and 3%, respectively, and mechanically stirred at 100 rpm and 60° C. for 24 h. After being washed with deionized water, the membrane was dried in a 60° C. forced air drying oven for 10 min to obtain carboxyl-metal ion complex anti-pollution nanofiltration membranes under different conditions, which were respectively recorded as Example 1, referred to as M1; Example 2, referred to as M2; and Example 3, referred to as M3.
[0035] Performance Test 1: Surface morphology and elemental analysis
[0036] A comparative test was conducted on conventional polyamide nanofiltration membranes without calcium chloride modification and polyamide nanofiltration membranes modified with calcium chloride of different concentrations. The surface morphology of the control sample and the modified sample was observed using a scanning electron microscope (SEM). The results are as follows: Figure 1 As shown in the figure, the coating of divalent metal ions will increase the roughness of the membrane surface and the specific surface area of the membrane, which is beneficial to the improvement of the membrane permeability.
[0037] A comparative test was conducted between conventional polyamide nanofiltration membranes without calcium chloride modification and polyamide nanofiltration membranes modified with different concentrations of calcium chloride, and the active layers of the control sample and the modified sample were analyzed using X-ray photoelectron spectroscopy (XPS). Figure 2 As shown in the figure, calcium element is indeed introduced into the surface of the membrane. With the increase of calcium chloride concentration in the modification process, the calcium content in the elemental analysis results of the membrane surface also increases linearly, with the highest calcium content being 4.7% and the lowest being 0.3%. It is precisely because of the appearance of calcium element on the membrane surface that the contact angle of the membrane surface is effectively reduced and the hydrophilicity of the membrane surface is enhanced, which not only improves the anti-pollution performance, but also increases the flux of the membrane.
[0038] Performance test 2: membrane flux test
[0039] The pure water flux of the prepared nanofiltration membrane was measured using a high-pressure membrane performance test device, and the operation was as follows. The membrane samples were cut into square membrane surfaces with a side length of 2.5 cm, and then placed in the stainless steel test tank of the high-pressure membrane performance test device, and the screws of the test tank were tightened; the water temperature constant box was controlled at 26°C, the pressure was adjusted to 10 bar, and the pre-pressure was performed for 1 hour; after the pre-pressure was completed, the mass of the empty beaker was first measured, and then the water was collected at one end of the membrane outlet of the test tank with an empty beaker for 15 minutes, and three parallel tests were performed, and then the pure water flux of the membrane was calculated according to the formula.
[0040] After testing, the fluxes of M1, M2 and M3 obtained in Example 1 are significantly improved compared with M0, and the flux improvement is the largest in M1, which is 27.89% higher than that of M0.
[0041] Embodiment 4:
[0042] A method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane, the specific steps are as follows:
[0043] (1) The polyamide nanofiltration membrane was soaked in deionized water for 24 h, and then soaked in anhydrous ethanol for 2 h to remove impurities on the membrane surface; the pretreated polyamide nanofiltration membrane was placed in a polytetrafluoroethylene sealed box (single-sided reaction box), 0.3 g / L dopamine and 0.9 g / L polyethyleneimine were added, and the pH was adjusted to 8.5 using Tris-HCl (50 mM), and then placed in a shaker, and reacted at 80 rpm and 40°C for 1.5 h until a yellow-brown PDA / PEI layer appeared on the membrane; then it was rinsed with deionized water for three more times and blown dry with N2 to obtain a dopamine / polyethyleneimine-coated polyamide nanofiltration membrane.
[0044] (2) preparing 80 mL of anhydrous ethanol solution of succinic anhydride at a concentration of 5 g / L, and then immersing the obtained dopamine / polyethyleneimine coated polyamide nanofiltration membrane in the anhydrous ethanol solution of succinic anhydride, and mechanically stirring at 150 rpm and 25° C. for 12 h; after washing with deionized water, drying in a forced air drying oven at 60° C. for 10 min, obtaining a polyamide nanofiltration membrane having carboxyl functional groups on the surface.
[0045] (3) A calcium chloride solution with a mass concentration of 1% was prepared, and the polyamide nanofiltration membrane containing carboxyl functional groups on the surface was immersed in the calcium chloride solution, and mechanically stirred at 150 rpm and 50° C. for 12 h. After being washed with deionized water, it was dried in a 60° C. forced air drying oven for 10 min to obtain a carboxyl-metal ion complex anti-pollution nanofiltration membrane, which was recorded as Example 4, referred to as M4.
[0046] Embodiment 5:
[0047] A method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane, the specific steps are as follows:
[0048] (1) The polyamide nanofiltration membrane was soaked in deionized water for 24 h, and then soaked in anhydrous ethanol for 2 h to remove impurities on the membrane surface; the pretreated polyamide nanofiltration membrane was placed in a polytetrafluoroethylene sealed box (single-sided reaction box), 0.2 g / L dopamine and 0.3 g / L polyethyleneimine were added, and the pH was adjusted to 8.5 using Tris-HCl (50 mM), and then placed in a shaker, and reacted at 150 rpm and 40°C for 0.5 h until a yellow-brown PDA / PEI layer appeared on the membrane; then it was rinsed with deionized water three times and blown dry with N2 to obtain a dopamine / polyethyleneimine-coated polyamide nanofiltration membrane.
[0049] (2) preparing 80 mL of anhydrous ethanol solution of succinic anhydride at a concentration of 0.5 g / L, and then immersing the obtained dopamine / polyethyleneimine coated polyamide nanofiltration membrane in the anhydrous ethanol solution of succinic anhydride, and mechanically stirring at 300 rpm and 30° C. for 36 hours; after washing with deionized water, drying in a forced air drying oven at 60° C. for 10 minutes, obtaining a polyamide nanofiltration membrane having carboxyl functional groups on the surface.
[0050] (3) A calcium chloride solution with a mass concentration of 3% was prepared, and the polyamide nanofiltration membrane containing carboxyl functional groups on the surface was immersed in the calcium chloride solution, and mechanically stirred at 50 rpm and 40° C. for 36 h. After being washed with deionized water, it was dried in a 60° C. forced air drying oven for 10 min to obtain a carboxyl-metal ion complex anti-pollution nanofiltration membrane, which was recorded as Example 5, abbreviated as M5.
[0051] The experimental results of Examples 4 and 5 are similar to the experimental results of Examples 1 to 3, and are significantly improved over the result of Comparative Example 1.
[0052] In summary, in the present invention, by loading negatively charged functional groups on the membrane surface, and then depositing divalent metal salt ions on the membrane surface through covalent bonds and electrostatic attraction, the positively charged metal ions are loaded on the membrane surface. The covalent bonding and electrostatic attraction make the bonding very firm and not easy to fall off, and also have a good anti-pollution effect when the water quality and water volume fluctuate greatly. The modification method of the present invention significantly improves the water flux of the membrane, which is more than 20% higher than that before modification. At the same time, the method adopted by the present invention is simple and easy to operate, the reaction is mild, and the raw materials used are relatively economical and environmentally friendly, which is conducive to reducing production costs and protecting the environment.
[0053] Finally, it should be noted that: although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation methods, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, these embodiments can be subjected to various changes, modifications, substitutions and variations without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a carboxyl-metal ion complex anti-pollution nanofiltration membrane, characterized in that: The following steps are involved: S1: Using a nanofiltration membrane as a base membrane, immersing one side of the base membrane in a polyphenol compound solution to react, so that a polyphenol compound layer is formed on its surface with abundant amino groups, and then washing with deionized water to obtain a surface functionalized base membrane; S2: soaking the surface functionalized base membrane obtained in step S1 in an organic solution containing an organic compound, stirring to allow the membrane surface to carry carboxyl groups, washing with deionized water and drying to obtain a nanofiltration membrane with carboxyl groups on the surface; S3: soaking the nanofiltration membrane with carboxyl groups on the surface obtained in step S2 in a water-soluble divalent metal salt solution, stirring the membrane to form a carboxyl-metal ion complex layer, washing and drying to obtain a carboxyl-metal ion complex nanofiltration membrane with anti-pollution properties.
2. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S1, the nanofiltration membrane is a polyamide nanofiltration membrane.
3. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S1, the concentration of the polyphenol compound solution is 0.5-2 g / L, the polyphenol compound solution is a mixed solution of dopamine and polyethyleneimine, and the mass ratio of dopamine to polyethyleneimine is 1:(1-3).
4. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S1, the reaction conditions are: rotation speed 80-150 rpm, reaction temperature 40° C., and reaction time 0.5-1.5 h.
5. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S2, the concentration of the organic solution containing the organic compound is 0.5-5 g / L.
6. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S2, the organic solution containing the organic compound is an anhydrous ethanol solution containing succinic anhydride.
7. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S2, the stirring conditions are: mechanical stirring, rotation speed 150-300 rpm, temperature 20-30° C., and stirring time 12-36 h.
8. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S3, the mass concentration of the water-soluble divalent metal salt solution is 1-3%.
9. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S3, the water-soluble divalent metal salt solution is a calcium chloride solution.
10. The method for preparing the carboxyl-metal ion complex anti-pollution nanofiltration membrane according to claim 1, characterized in that: In step S3, the stirring conditions are: mechanical stirring, rotation speed 50-150 rpm, temperature 40-60° C., and stirring time 12-36 h.
Citation Information
Cited By
Preparation method of nanofiltration membrane capable of selectively separating monovalent ions from divalent ions
CN122098300A